Comment on "A multidisciplinary overview of the lower Miño River terrace system (NW Iberian Peninsula)" by E. Méndez-Quintas et al. (10th November 2020) - Viveen, W.; Veldkamp, A.; van Balen, R.T.; Schoorl, J.M.; Sanjurjo-Sanchez, J.; Vidal-Romani, J.R.; Braucher, R.; Bourlès, D.
Abstract: The paper by E. Méndez-Quintas et al. (2020) aims to give an interdisciplinary overview of the lower Miño River terrace record in NW Iberia by combining geological and archaeological data. The authors also pretend to re-interpret the geological-geomorphological evolution of this river by presenting new data and by comparing them to data published in our five related papers. However, a wrong interpretation of the data they present as well as incorrect and selective citations of ours lead to the production of a publication containing numerous errors. The most flagrant ones are the mapping of fluvial terraces on one side of the river only and an incorrect interpretation of the sedimentological information used to correlate terrace remnants along-river. This results in incorrect longitudinal profile reconstructions and an improper proposal of the evolution of the Miño terraces that is even contradicted by the data they present. On the upside, the ages of the Porto Maior terrace site published by these authors confirm our previously published longitudinal profile reconstructions and evolutionary model of the Miño valley.